1997
DOI: 10.2337/diacare.20.4.472
|View full text |Cite
|
Sign up to set email alerts
|

Is the Quality of Diabetes Care Better in a Diabetes Clinic or in a General Medicine Clinic?

Abstract: Patients cared for by physicians in the diabetes clinic receive better quality of diabetes care than do patients cared for by physicians in the general medical clinic. If patient care is to be shifted from specialists to generalists, additional attention needs to be paid to ensure that generalists have the knowledge and system resources necessary to deliver an acceptable quality of diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 0 publications
5
80
3
1
Order By: Relevance
“…CONCLUSIONS -Our finding of low levels of adherence by PCPs to a broad array of diabetes guidelines is consistent with findings by other researchers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Prior studies have demonstrated successful interventions to improve adherence to diabetes guidelines by PCPs.…”
Section: Analysessupporting
confidence: 80%
“…CONCLUSIONS -Our finding of low levels of adherence by PCPs to a broad array of diabetes guidelines is consistent with findings by other researchers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Prior studies have demonstrated successful interventions to improve adherence to diabetes guidelines by PCPs.…”
Section: Analysessupporting
confidence: 80%
“…Aunque en la última década muchas organizaciones han medido la calidad de la atención a los pacientes diabéti-cos (20)(21)(22)(23)(24)(25), QUALIDIAB es el primer proyecto de medición de forma cooperativa y simultánea implementado en seis países de América Latina.…”
Section: Discussionunclassified
“…However, a large body of literature has suggested that patients with diabetes are not receiving appropriate care (10)(11)(12)(13). Efforts introduced by the National Committee for Quality Assurance (14) and the Diabetes Quality Improvement Project (15) to make health plans and medical groups more accountable for diabetes care have added pressure to address deficiencies in diabetes care.…”
Section: Pharmacy Datamentioning
confidence: 99%